2009
DOI: 10.2147/opth.s5328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prostaglandin analog therapy on the ocular surface of glaucoma patients

Abstract: Purpose: To quantify changes in tear break-up time (TBUT), corneal staining and ocular surface disease index (OSDI) in glaucoma patients after switching therapy from latanoprost with 0.02% benzalkonium chloride (BAK) to travoprost with sofZia ™ . Methods: Prospective consecutive case series evaluating patients before and 8 weeks after switching from latanoprost with BAK to travoprost with sofZia ™ in patients with baseline TBUT less than 6 seconds.Results: Forty eyes of 20 consecutive patients using latanopros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
1
26
2
Order By: Relevance
“…Corneal staining can be readily observed at the ocular surface after exposure to toxic agents. For example, Horsley and Kahook reported reduced corneal staining when patients were switched from glaucoma eye drops containing benzalkonium chloride (a common preservative in ocular medications) to a similar drug not containing this agent [1] . Topical anesthetic drops are also associated with corneal staining [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Corneal staining can be readily observed at the ocular surface after exposure to toxic agents. For example, Horsley and Kahook reported reduced corneal staining when patients were switched from glaucoma eye drops containing benzalkonium chloride (a common preservative in ocular medications) to a similar drug not containing this agent [1] . Topical anesthetic drops are also associated with corneal staining [2] .…”
Section: Introductionmentioning
confidence: 99%
“…BAK is an antimicrobial preservative commonly used in topical ophthalmic preparations that acts by disrupting microbial cell membranes and promoting cell death. 2 , 25 The use of BAK in ophthalmic solutions, however, has demonstrated a number of disadvantages in both in vitro and in vivo models, including dose-dependent and time-dependent toxicity to the corneal epithelium, the conjunctival epithelium, the stroma, and tear film constituents. 25 41 BAK may reduce epithelial cell integrity, impair healing, induce cytokine secretion, cause elevated production of conjunctival inflammatory cells, and reduce goblet cell numbers.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 25 The use of BAK in ophthalmic solutions, however, has demonstrated a number of disadvantages in both in vitro and in vivo models, including dose-dependent and time-dependent toxicity to the corneal epithelium, the conjunctival epithelium, the stroma, and tear film constituents. 25 41 BAK may reduce epithelial cell integrity, impair healing, induce cytokine secretion, cause elevated production of conjunctival inflammatory cells, and reduce goblet cell numbers. Further, BAK may impair tear function and reduce tear film integrity through its effects on the integrity of the meibomian layer and disruption of the lipid film continuous multilayer structure, thus decreasing tear film break-up time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New PG formulations without BAC or with alternative preservatives are currently in development. Several studies have revealed that alternative preservatives to BAC, for example sofZia (Alcon, Fort Worth, TX, USA), Purite (a stabilized oxychloro complex), and Polyquad, produce fewer corneal changes and less conjunctival inf lammation than BAC [ 1 - 3 , 14 , 15 ]. Preservative-free PGs are currently commercially available, and their low toxicity to the corneal and conjunctival surfaces has been confirmed [ 4 ].…”
mentioning
confidence: 99%